Integrated electronic health record facilitates a safer and more efficient rural outreach haematology service. Issue 11 (23rd October 2021) - Cashman, Helen; Mayson, Eleni; Kliman, David; Kesby, Janet; Bell, Jennifer; Vachalec, Sue; Withers, Barbara; Lavee, Orly; Milliken, Sam; Moore, John; Hamad, Nada
Abstract: Background: Rural Australian oncology patients are known to have inferior mortality rates compared to metropolitan patients, possibly related to access to appropriate healthcare services and treatments. Electronic systems improve the safety of chemotherapy administration and allow easily accessible patient information and data collection. Aims: To integrate the electronic healthcare delivery systems at a metropolitan hospital and a rural outreach haematology clinic to facilitate streamlined and safe outpatient care. Methods: The MOSAIQ v2.64(Elekta) system utilised at St Vincent's Hospital was introduced at a linked rural outreach haematology clinic. The two separate comprehensive practice management systems incorporating all patient information were consolidated into one, becoming accessible from both sites. Results: The electronic systems were successfully integrated between the two sites in October 2017. Electronic chemotherapy prescribing at the Griffith site is now guided by inbuilt, pharmacist‐reviewed protocols thereby improving the safety and flexibility of remote prescribing. The centralised electronic health record has improved streamlined care during patient transitions between the two hospitals with enhanced continuity of documentation and management. Increases in total clinic patients and appointment numbers are demonstrable since implementation, and sustained during the COVID‐19 pandemic. Conclusion: The present study provides a novel example of the successful implementation of a centralised electronic healthcare record and chemotherapy prescribing system in a haematology setting shared between a metropolitan service and a rural outreach hospital clinic. This has positive implications for the safety and efficiency of healthcare delivery at the rural site applicable to all linked rural Australian clinics, as well as allowing data collection to assist future planning of the service.